The The Impact of a Cashless Payment System on Inflation - muslikhati muslikhati; Fitrian Aprilianto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2022)
The rise of transactions without using money or what is commonly referred to as cashless transactions. Cashless transactions have several advantages, namely, functional, effortless, and quick. In addition, cashless transactions get an impact on monetary policy in Indonesia. The convenience obtained when conducting cashless transactions results in the acceleration of the velocity of money. Although the number of cash transactions in the community has decreased, the rate of money creates a high intensity with the use of cashless transactions. If the power of money circulation is high, it is feared that it will cause inflationary effects. This study aims to determine the impact of the cashless payment system on inflation. A quantitative approach was used in this study with secondary data which in the source obtained through documentation techniques obtained from Bank Indonesia (BI) and the Central Statistics Agency (BPS). from January 2009 until December 2020. The analysis technique uses multiple linear regression analysis. The results showed that the electronic-money variables had a significant negative effect, the debit card variables had a significant positive impact, the credit card variables had an insignificant negative effect, and the interest rate variables had a significant positive impact.